Motivation and climate change: A review. (December 2021) - Brick, Cameron; Bosshard, Anna; Whitmarsh, Lorraine
Abstract: This paper reviews motivations people experience about climate change and integrates recent findings into the BUCkET model of core social goals. We argue that environmentalism is not the main cause of thoughts or behaviors about climate change. Rather, the evolved social needs for Belongingness, Understanding, Control, self-Enhancement, and Trust are more practical intervention targets than the attempt to create environmentalist beliefs or identities. We used database searches to identify the key research areas on motivation and climate change and synthesized articles into the BUCkET model. This reveals some limiting assumptions of previous approaches and suggests the effectiveness of targeting existing motives rather than fostering new values or worldviews.